Comparação da resistência de união de sistemas adesivos em diferentes substratos dentinários - Nicoloso, Gabriel Ferreira (2015)
Recently, a new category of adhesive systems has been proposed to perform restorative procedures. These adhesives, named as universal have been released in the market with the purpose to decrease the technique sensitivity, likewise they offer a great versatility in the procedure as can be applied to tooth structures in both application modes. The objective of this dissertation is to present two papers. The first article aimed to compare the bond strength of a universal adhesive (Scotchbond Universal Adhesive) applied in both application modes to its controls, Adper Single Bond 2 and Clearfil SE Bond, when bonded to caries-affected primary and permanent dentin. The second article compared the bond strength of the Scotchbond Universal Adhesive in both application modes to the same controls aforementioned to caries-affected and sound permanent dentin. Forty-eight permanent teeth and twenty-four primary teeth were selected to perform the experiments in both papers. All teeth had their mid-coronal dentin surfaces exposed by removing the occlusal third. The dentin surfaces, which represent caries-affected dentin substrate, were submitted to pHcycling. The other teeth, sound dentin, remained intact until the bonding procedure. Specimens were randomly allocated (n=6) according to the adhesives tested and conditions of the dentin. After bonding procedures, a composite core was build-up to a height of 4-5mm and then was sectioned perpendicular to the adhesive interface in order to obtain rectangular sticks (0.8 mm2) that were submitted to microtensile tests (1mm/min). Two-way Analysis of Variance and post-hoc Tukey´s test (α = 0.05) were performed as statistical analysis. In the first paper, the universal adhesive, Scotchbond Universal Adhesive, presented statistically similar bond strength values to its controls in both dentin substrates, likewise the different substrates did not differ in bond strength values. In the second paper, adhesives bonded to sound dentin presented higher bond strength values compared with caries-affected dentin, but none of the adhesives tested presented statistically significant differences. The new universal adhesive, Scotchbond Universal Adhesive, can be applied in both application modes without the concern of compromise the bonding performance on resin composite restorations.